Inhibiting crosstalk between MET signaling and mitochondrial dynamics and morphology: a novel therapeutic approach for lung cancer and mesothelioma. Issue 11 (2nd November 2018) - Wang, Jiale; Mirzapoiazova, Tamara; Carol Tan, Yi-Hung; Pang, Ka Ming; Pozhitkov, Alex; Wang, Yingyu; Wang, Yang; Mambetsariev, Bolot; Wang, Edward; Nasser, Mohd W.; Batra, Surinder K.; Raz, Dan; et al.
ABSTRACT: The receptor tyrosine kinase MET is frequently involved in malignant transformation and inhibiting its activity in MET-dependent cancers is associated with improved clinical outcomes. Emerging evidence also suggests that mitochondria play an essential role in tumorigenesis and Dynamin Related Protein (DRP1), a key component of the mitochondrial fission machinery, has emerged as an attractive therapeutic target. Here, we report that inhibiting MET activity with the tyrosine kinase inhibitor MGCD516 attenuates viability, migration, and invasion of non-small cell lung cancer (NSCLC) and malignant pleural mesothelioma (MPM) cell lines in vitro, and significantly retards tumor growth in vivo . Interestingly, MGCD516 treatment also results in altered mitochondrial morphology in these cell lines. Furthermore, inhibiting MET pharmacologically or knocking down its expression using siRNA, decreases DRP1 activity alluding to possible crosstalk between them in these two cancers. Consistently, a combination of MGCD516 and mdivi-1, a quinazolinone reported to inhibit mitochondrial fission, is more effective in attenuating proliferation of NSCLC and MPM cell lines than either drug alone. Considered together, the present study has uncovered a novel mechanism underlying mitochondrial regulation by MET that involves crosstalk with DRP1, and suggests that a combination therapy targeting both MET and DRP1 could be a novel strategy for NSCLC and MPM.